Benefits of a Balance Exercise Assist Robot in the Cardiac Rehabilitation of Older Adults with Cardiovascular Disease: A Preliminary Study - Kakeru Hashimoto; Akihiro Hirashiki; Kenichi Ozaki; Koki Kawamura; Junpei Sugioka; Shunya Tanioku; Kenji Sato; Ikue Ueda; Naoki Itoh; Kenichiro Nomoto; Manabu Kokubo; Atsuya Shimizu; et al. (Journal of Cardiovascular Development and Disease, 2022)
We examined whether adding robot-supported balance exercises to cardiac rehabilitation improves the ability to balance in older adults with cardiovascular disease (CVD). We conducted a prospective study in 52 older adults who had been hospitalized for worsening CVD. Once weekly for four months, for a total of sixteen sessions as outpatients, the subjects used a Balance Exercise Assist Robot (BEAR) to perform balance exercises and an ergometer for aerobic exercises. Participants’ mean age was 76.9 ± 6.8 years (range, 65–95 years), and their mean brain natriuretic protein level was 164.0 ± 190.0 pg/mL. After the intervention, participants showed significant improvements in gait speed (before, 1.06 ± 0.33 m/s; after, 1.23 ± 0.30 m/s; p < 0.001), Short Physical Performance Battery score (before, 10.02 ± 2.25; after, 10.88 ± 1.79; p ˂ 0.001), timed up-and-go (before, 11.11 ± 5.07 s; after, 9.45 ± 3.45 s; p ˂ 0.001), and knee extension (before, 26.97 ± 11.78 kgf; after, 30.13 ± 13.04 kgf; p = 0.001). Cardiac rehabilitation including exercises using BEAR improved physical functioning and the ability to balance in older adults with CVD. Frail and prefrail patients improved, whereas robust ones did not change.